Local Food for Lewiston: Exploring the Role of Food Assessment as Part of Broader Work in Community-engaged Food Systems - Walter, Kirsten (Maine Policy Review, 2011)
Kirsten Walter’s case study discusses the community food assessment in Lewiston, Maine and the recommendations stemming from it.